Pengembangan Organisasi Pembelajar di Pesantren Modern: Studi Lapangan Penerapan Lima Disiplin Learning Organization Peter Senge di Pondok Modern Darussalam Gontor Kampus 7 - Iqbal Mustofa Fathurrahman; Megawati; Subandi; Heru Juabdin Sada; Patonah (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Social change, technological development, and increasing demands for educational quality require educational institutions to continuously adapt and engage in sustainable learning. In this context, the concept of a learning organization is highly relevant, including in modern Islamic boarding schools. This study aims to analyze the implementation of the learning organization concept at Pondok Modern Darussalam Gontor Campus 7 using Peter Senge’s five disciplines: personal mastery, mental models, shared vision, team learning, and systems thinking. This research employed a qualitative field research approach. Data were collected through in-depth interviews, observations, and documentation involving KMI leaders, educational staff, and teachers. The findings reveal that Pondok Modern Darussalam Gontor Campus 7 has implemented all five disciplines in an integrated manner within its learning system and institutional management. These results indicate that modern Islamic boarding schools have strong potential to develop as adaptive and sustainable learning organizations in response to contemporary educational challenges.